The effect of sucrose polymer-size on glass transition temperature, glass former fragility, and water retention during drying - Kumara, U. G. V. S. S.; Ramirez, John F.; Boothby, Thomas C. (Frontiers in Materials, 2024)
Water is essential for all active life processes. Despite this, there are a number of organisms that can survive prolonged desiccation. The vitrification hypothesis posits that such organisms survive desiccation by forming non-crystalline amorphous (vitrified) solids, often through the accumulation of protective disaccharides. In line with this theory, vitrification has been shown to be essential for desiccation tolerance in many organisms that survive extreme drying. However, it is known that not all vitrified materials are protective and that certain physio-chemical properties correlate with the protection in the glassy state. Furthermore, recent evidence suggests that the physio-chemical properties that correlate with protection can vary depending on the chemical nature of similarly sized protectants. While the chemistry of protectants has been probed in relation to the protective properties they induce when vitrified, the effect of protectant size on glassy properties and protection during drying has not been investigated. Here, we study the effect of the polymer size of sucrose on glassy properties associated with protection in the vitrified state. The monomer sucrose, and the polymers polysucrose 70 and polysucrose 400 (70 and 400 refer to the molecular weight of the polymers in kDa). Using these three different-sized sucrose polymers, we find that each of the glassy properties we investigated including; enzyme protection, water content, glass transition temperature, and glass former fragility, were affected by polymer size. However, only one vitrified property, glass transition temperature, correlated with protection during drying. This correlation is heavily dependent on sucrose polymer size. Increased glass transition midpoint temperature correlated positively with protection conferred by monomeric sucrose (p-value = 0.009, R2 = 0.840), whereas this correlation was bi-phasic for polysucrose 70, and had an inverse relationship for polysucrose 400 (p-value = 0.120, R2 = 0.490). Our results indicate that the size of vitrifying protectants can have a profound effect on glassy properties as well as on how these properties correlate with protection in the dry state. Beyond desiccation tolerance, these findings provide insights for the development of new technologies for the stabilization of biological material in the dry state.